From angiotensin-converting enzyme 2 disruption to thromboinflammatory microvascular disease: A paradigm drawn from COVID-19. (1st March 2021) - Vinci, R.; Pedicino, D.; Andreotti, F.; Russo, G.; D'Aiello, A.; De Cristofaro, R.; Crea, F.; Liuzzo, G.
Abstract: We concisely review clinical, autopsy, experimental and molecular data of 2019 coronavirus disease (COVID-19). Angiotensin-converting enzyme 2 disruption and thromboinflammatory microangiopathy emerge as distinctive features. Briefly, entry of the virus into microvessels can profoundly disrupt the local renin-angiotensin system, cause endothelial injury, activate the complement cascade and induce powerful thromboinflammatory reactions, involving, in particular, von Willebrand factor, that, if widespread, may lead to microvascular plugging, ischemia and, ultimately, organ failure. We believe the current COVID-19 data consolidate a widely unrecognised paradigm of potentially fatal thromboinflammatory microvascular disease. Highlights: SARS-CoV-2 entry into microvessels can disrupt the local renin-angiotensin-system. Complement and von Willebrand factor overexpression occur in COVID-19. COVID-19 patients show widespread thromboinflammatory microvascular disease. COVID-19 provides an important paradigm of potentially fatal microangiopathy.